1986
DOI: 10.1159/000118322
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effects of lonophores and Inhibitors of Main Sodium and Calcium Movements on Tyrosine and Tryptophan Transport by Human Erythrocytes

Abstract: Peripheral models using blood cells might be biochemical markers in various psychiatric illnesses. In previous papers we reported a deficit of tyrosine and tryptophan transport in red cells incubated in plasma from depressed patients. In the present study we investigated the role played by sodium and calcium in these transports by using inhibitors and ionophores of the main movements of these electrolytes. We also studied the contribution of phloretin-sensitive countertransport, which has been described as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our results showed disturbances of these transports accord ing to clinical subgroups of patients, (DSM III classifica tion), as compared with controls. The aim of our general study is to facilitate the drug therapy, with maximum benefit to the patients [Bovier et al, 1988a[Bovier et al, , 1988b; Azorin et al, 1990], In parallel with clinical applications, we attempted to characterize better these peripheral trans port mechanisms by using inhibitors of electrolyte move ments, such as phloretin, furosemide, ouabain, nonactin, A 23387 and others, and by studying the involvement of the membrane fluidity [Widmer et al, 1986[Widmer et al, . 1987, Recently, we found that sulfhydric reagents such as parachloromercuribenzenesulfonate, a nonmembranepenetrating agent, or N-ethylmaieimide, inhibited the transport of both amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed disturbances of these transports accord ing to clinical subgroups of patients, (DSM III classifica tion), as compared with controls. The aim of our general study is to facilitate the drug therapy, with maximum benefit to the patients [Bovier et al, 1988a[Bovier et al, , 1988b; Azorin et al, 1990], In parallel with clinical applications, we attempted to characterize better these peripheral trans port mechanisms by using inhibitors of electrolyte move ments, such as phloretin, furosemide, ouabain, nonactin, A 23387 and others, and by studying the involvement of the membrane fluidity [Widmer et al, 1986[Widmer et al, . 1987, Recently, we found that sulfhydric reagents such as parachloromercuribenzenesulfonate, a nonmembranepenetrating agent, or N-ethylmaieimide, inhibited the transport of both amino acids.…”
Section: Introductionmentioning
confidence: 99%